2020
DOI: 10.3390/su12197843
|View full text |Cite
|
Sign up to set email alerts
|

Impact and Acting Path of Carbon Emission Trading on Carbon Emission Intensity of Construction Land: Evidence from Pilot Areas in China

Abstract: Recently, the environmental and resource crisis caused by excessive energy consumption has aroused great concern worldwide. China is a major country of energy consumption and carbon emissions, and has attempted to build a carbon emission trading market to reduce carbon emissions. This practice helps to promote the carbon trading projects for both regional carbon emission reduction and sustainable development in the pilot areas, as well as having important theoretical and practical significance for the further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…The research based on the “Porter Hypothesis” holds that environmental equity instruments can stimulate innovation, generate an innovation compensation effect and raise energy efficiency. Based on the panel data of 30 provinces in China, the empirical study found that environmental regulation and environmental innovation have a direct, positive effect on energy efficiency [ 35 ], which is consistent with the research results of Lin and Jia [ 36 ] through case analysis. Some other scholars believe that there is a nonlinear relationship between environmental regulation and energy efficiency, mainly due to the two natural attributes of “scarcity” and “externality” of energy, which makes the leading force affecting energy efficiency evolve from the “innovation compensation effect” to the “cost following effect” [ 37 ].…”
Section: Literature Reviewsupporting
confidence: 70%
“…The research based on the “Porter Hypothesis” holds that environmental equity instruments can stimulate innovation, generate an innovation compensation effect and raise energy efficiency. Based on the panel data of 30 provinces in China, the empirical study found that environmental regulation and environmental innovation have a direct, positive effect on energy efficiency [ 35 ], which is consistent with the research results of Lin and Jia [ 36 ] through case analysis. Some other scholars believe that there is a nonlinear relationship between environmental regulation and energy efficiency, mainly due to the two natural attributes of “scarcity” and “externality” of energy, which makes the leading force affecting energy efficiency evolve from the “innovation compensation effect” to the “cost following effect” [ 37 ].…”
Section: Literature Reviewsupporting
confidence: 70%
“…They found that this policy restrains emission intensity by prompting industrial structure optimization and energy intensity reductions and that this effect is increasing year on year. Li et al (2020) also confirmed that the ETS reduces the proportion of the added value of the secondary industry in GDP, promotes regional industrial structure optimization, and reduces the intensity of regional carbon emission. From the perspective of the efficiency improvement mechanism, Feng et al (2020) investigated the impact of China's SO 2 ETS on total factor productivity at the enterprise level.…”
Section: Literature Reviewmentioning
confidence: 93%
“…In order to promote the sustainable development of wind and solar energy and other new energy industries, the government began to try out the Tradable green certificate (TGC) (hereinafter referred to as "green certificate") and carbon emission trading system [3]. Green certificate is a means to monetize the environmental value of renewable energy, and it is a negotiable and tradable securities [4]. Carbon emission rights trading treats excess carbon emissions as commodities, and while restricting carbon emissions through the quota system, it also uses market means to improve the competitiveness of low-carbon industries and promote the development of renewable energy power generation [5].…”
Section: A Motivationmentioning
confidence: 99%